Narratives: unveiling teachers’ identities - Marimar da Silva; Saionara Greggio; Camila Araújo de Lucena; Didiê Ana Ceni Denardi; Gloria Gil (Signum: Estudos da Linguagem, 2007)
This study aims at reporting the results of a qualitative interpretative research on English as a foreign language teachers’ practical knowledge. More specifically, the objective was to identify the teachers’ rules and principles of practice, through life-story narratives. The result was a set of biographical stories through which the participants themselves could make meaningful connections between moments of their lives and their practical knowledge. The research process as a whole offered the participants a fruitful context for reflection on their professional identities as teachers and the bits and pieces of the unknown identities turned to be a bit more known. Finally, this study points out that life-story narratives can open a window into teachers’ practical knowledge, which may mean an alternative to possible changes on cognitive and/or behavioral level if introduced as a tool for reflection in early stages of teacher education programs.